USING ARTIFICIAL INTELLIGENCE AND COMPETITIVE ADVANTAGE IN OPERATIONS MANAGEMENT: A CASE STUDY OF ISLAMIC BANKS IN AMMAN, JORDAN - Khaled Abdulwahab Alzeaideen; Ala’a Abdulkarim Hamdan; Hazem Khaled Shehadeh; Majed Abdel-Mohdi Masadeh; Hala Alsabatin; Abdalmuttaleb Al-Sartawi; Waleed Nureldeen (Operational Research in Engineering Sciences: Theory and Applications)
This study seeks to examine the impact of utilising artificial intelligence (AI) including genetic algorithms, expert systems, neural networks, and intelligent agents on key dimensions of competitive advantage, namely cost, quality, delivery, and flexibility, within Islamic banks operating in the Governorate of Amman. Adopting a descriptive-analytical approach, the study employed a structured questionnaire as the primary instrument for data collection. The questionnaire was administered to employees of Islamic banks, who comprise the study population (N = 3,339), with a stratified random sample of 437 individuals selected for participation. A total of 371 valid responses were obtained and subsequently analysed using SPSS to conduct hypothesis testing. The results reveal a statistically significant effect of AI adoption in banking operations on the competitive advantage dimensions under investigation. These findings underscore the pivotal role AI plays in enhancing competitive positioning. Accordingly, the study recommends the strategic implementation of AI technologies to improve cost estimation accuracy, minimise operational waste, monitor service delivery timelines, and foster the development of innovative and flexible Islamic financial services. This study integrates artificial intelligence techniques into service performance evaluation to support data-driven decision making in banking operations.